Polymorphism and fighting in male fig wasps - Vincent, Stephanie Louise (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1992)
Male fig wasps (Hymenoptera: Chalcidoidea) exhibit a fascinating range of morphology and behaviour. A cluster analysis, based on descriptions of the males of several hundred species, distinguished six major morphological groups. Behaviourial observations suggest that male morphology is related to the levels of inter-male aggression. Three behaviourial groupings were identified. Fighting species generally mated in the fig cavity, pacifist species mated in the females' galls or outside the figs. Mating sites are thus the primary determinants of male morphology and behaviour. In fighting species males were larger than their females, whereas pacifists and aggressors were equal in size or smaller than conspecific females. The large males in fighting fig wasps appear to be a consequence of sexual selection because larger males tended to win fights. Within a species there were no differences in the size of the galls that produced males and females, even in species where sexual size differences were present, suggesting that there is a heritable component to wasp size. No alternative advantages for smaller males were detected. Although fights were sometimes fatal, damage was not always a consequence of fighting behaviour and was recorded in both fighting and pacifist species. Sex ratios in several species were more female biased at higher population densities. Sex ratios of species with 'internally' ovipositing species were heavily female biased, but approached 1:1 in more outbred species with 'externally' ovipositing females. Levels of matedness, among females ranged from 73% to 99%. No evidence for sperm exhaustion was obtained. Species of Philotrypesis with both winged and flightless males were present only in southern African Ficus species from subsections Platyphyllae and Chlamydodorae. No species had only winged males. The flightless males of some Philotrypesis species were themselves polymorphic. In one polymorphic Philotrypesis species, winged males were found to be rare at high densities, but common at low densities. Digitata and religiosa males of Otitesella differed in coloration, size and behaviour. Digitata males were aggressors while religiosa males were fighters. Digitata males escaped from the figs whereas religiosa males remained inside the figs, perhaps because only digitata males were attracted to Light. Proportionally more digitata than religiosa males were present in low density populations and females were found to respond differently to the two morphs.
Keywords: Fig waspChalcid wasps -- MorphologyWasps